Equilibrium processes in biomedical data analysis: the Wright–Fisher model - Koroliouk, D.; Koroliuk, V.S.; Rosato, N. (Кибернетика и системный анализ, 2014)
The biological process of cooperative interaction with equilibrium state will be described as a model of binary statistical experiments with Wright–Fisher normalization, which sets the concentration of a certain characteristic. Such mathematical model is supposed to have a property of persistent regression which means that all current elementary transitions depend on the mean concentration of the said characteristics in the previous state. Equilibrium state of the model is expressed in the terms of the regression function, given by a cubic parabola with three real roots. We construct stochastic approximation of the model by autoregressive process with normal disturbances. Such approach was developed for effective and calculable mathematical description of dynamic concentration for experiment planning, parameters evaluation and hypotheses verification of mechanism of action.